Stuart Appelle 1946-2011 - Bullard, Eddie (Journal of Scientific Exploration, 2012)
<!–[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> Stuart Appelle pursued two intellectual careers with distinction. He was a professor of psychology at the State University of New York College at Brockport, an experimental psychologist who published numerous professional papers in his specialty of tactile perception. Later he assumed various administrative positions at SUNY Brockport, among them chairman of the Department of Psychology and Dean of the School of Letters and Sciences. In his conventional academic pursuits his life was full and successful, but he devoted considerable time to another career that carried him out of ordinary academia into the realm of anomaly research. Since I knew him in this second capacity I will emphasize it even though his interest in UFOs comprised only one corner of a much larger whole. As early as 1972 while still a grad student, Stuart criticized a sociological “status inconsistency” explanation for UFO sightings in an article published in a scholarly journal [1]. His participation in UFO research began in earnest in the late 1980s as alien abductions rose to prominence as a topic of dispute. Psychological explanations for the nature of these experiences and the distress of people reporting them proliferated, but he saw considerable bad science and stepped in as a critic of speculative theories that paid little heed to the evidence. In a benchmark paper published in the Journal of UFO Studies he reviewed with systematic care the entire range of solutions, assessing such proposals as hypnotic suggestion, false memory, fantasy-proneness, and sleep anomalies for their strengths and exposing their shortcomings. He concluded that the conventional answers offered so far are insufficient to explain abductions and called for research that truly reckoned with the evidence [2]. A further development of his criticisms and arguments appeared in a chapter of Varieties of Anomalous Experience, published by the American Psychological Association in 2000 [3]. His co-authors were both prominent skeptics of abduction but he carried his case for the inadequacy of current research and theory throughout the chapter, thereby defending abduction as a potentially anomalous phenomenon in the mainstream scientific literature. He further defended the subject as worthy of scientific study in presentations at professional meetings.